Analysis of Public Satisfaction with Services at the Cileungsi Branch of BPJS Employment, Bogor Regency - Halimah Hasna Nabilah; Putri Allysa; Keysha Meivarani Vimico Putri; Budi Supriyatno (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2025)
The background of this research is the various obstacles experienced by the public in obtaining services at the Cileungsi Branch of the BPJS Ketenagakerjaan (Employment Social Security Agency), such as delays in recording contributions and a lengthy complaint process. The study aims to analyze the level of public satisfaction with services at the branch. The study used a descriptive qualitative approach with a population of thousands of active participants and 15–20 employees, and a purposive sample consisting of 4–6 employees and 3 participants. The main instruments were observation guidelines, interviews, and documentation. Data analysis was conducted through data reduction, presentation, and drawing conclusions using source triangulation for validity. The results showed that the public was generally satisfied with the service, especially in the dimensions of assurance and officer empathy. However, obstacles were found in the reliability and responsiveness of services due to the incompletely integrated digital system and human resource limitations. In conclusion, improving service quality can be achieved by digitizing the system, adding more staff, and training in communication and technology. This study provides recommendations for developing BPJS public services to be more responsive and accountable.